The world's fairs as spaces of global knowledge : Latin American archaeology and anthropology in the age of exhibitions (2018)
At the end of the nineteenth century, Brazil, Mexico, and Peru were among the countries participating in the most important world's fairs in Europe and North America. These mass gatherings focused on national self-images as well as technological development and commodities, but the Latin American exhibition organizers also understood them to be transnational spaces that contributed to the mobility of persons, objects, and knowledge. In this context, the scientific display of pre-Columbian 'antiquities' was regarded as being as important as the participation in archaeological and anthropological congresses. By understanding the world's fairs as 'spaces of global knowledge', this article highlights the agency of Latin American scientists, intellectuals, and collectors in the transnational endeavour to create a 'Latin American antiquity' at the fairgrounds. Although most fair attendees sought to study and display the pre-Columbian past in an objective manner, the older dream of (re-)constructing the splendour of America's ancient civilizations never completely vanished. © Cambridge University Press 2018.